What Makes Queer Oral History Different. (1st April 2016) - Murphy, Kevin P.; Pierce, Jennifer L.; Ruiz, Jason
Abstract: This essay asks whether queer oral history is different in light of recent interventions in queer theory, LGBTQ history, and oral history. It explores the intellectual genealogy of queer oral history in the research projects of some of its early practitioners. It also provides a close reading of Alessandro Portelli's classic essay and considers its implications for a queer methodology, drawing from the work of recent scholarship in queer studies as well as our collaborative research in the Twin Cities Gay, Lesbian, Bisexual, and Transgender Oral History Project. Finally, it gestures towards some of the unique dimensions of a queer methodology and its rich potential for research in LGBTQ oral history.